EXECUTIVE STRATEGIC LEADERSHIP AFFECTING THE EFFECTIVENESS OF SMALL SCHOOLS NAKHON SI THAMMARAT PRIMARY EDUCATIONAL SERVICE AREA OFFICE 4 - Ngamwuttichai, Tossapol; Chanakul, Benjaporn; Chairueng, Nopparat (Journal of MCU Nakhondhat, 2023)
The purpose of this research was to study strategic leadership. study the effectiveness of educational institutions Study the impact of strategic leadership on school effectiveness. and to study the approaches for developing strategic leadership of school administrators that affect the effectiveness of small educational institutions. Nakhon Si Thammarat Primary Educational Service Area Office 4 using a survey research model The sample group was teachers and personnel. Under the Office of Nakhon Si Thammarat Primary Educational Service Area 4, the sample group was selected by stratified random sampling technique. The district group where the school was located was used as the total random strata.A total of 214 people analyzed data using statistics, percentage, mean, standard deviation. Pearson’s correlation coefficient and multiple regression analysis. Nakhon Si Thammarat Primary Educational Service Area Office 4 overall was at a high level. The organizational culture building had the highest average. 1) The effectiveness of small educational institutions. Primary Educational Service Area Office Nakhon Si Thammarat District 4 overall was at a high level. The atmosphere and environment of the school 2) the effectiveness of small educational institutions Primary Educational Service Area Office Nakhon Si Thammarat District 4 overall was at a high level. Atmosphere and environment of the school have the highest average 3) Strategic leadership of school administrators in terms of organizational direction determination and strategic control and evaluation. affecting the effectiveness of small educational institutions Office of Nakhon Si Thammarat Primary Educational Service Area, Region 4 with a statistical significance at the .01 level. 4) Good administrators must be able to see the overall organization clearly. have a far-reaching vision The goal is clear, there is initiative in formulating strategies according to the specified educational standards. Participatory education management There is a network of potential co-organizers. Motivate teachers equally If the executive has the ability, there will be credibility. It has the power to drive and can develop quickly.